2011
DOI: 10.1093/geronb/gbr080
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Suicidal Ideation, and Reasons for Living among Older Adults

Abstract: The findings highlight the complexity of risk and protective factors for suicide and suggest that a thorough assessment of suicidal potential among older adults should include attention to their underlying personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 26 publications
4
52
3
1
Order By: Relevance
“…In regression analyses, borderline and histrionic were the only personality disorders features that contributed significant variance in suicidal ideation, whereas neuroticism was the only personality trait that contributed significant variance in suicidal ideation. 18 Here the researchers found highly significant (p=.0001) differences among cases and controls associated with adjustment disorder (case 29.2%, control 0.9%), mood disorder (case 12.4%, control 0.0%) and mood episode (case 8.0, control 0.9) . WHO/ISBRA study revealed the similar scenario, of the 1863 persons included in the WHO/ISBRA study, 292 had both a history of depressive symptoms and alcohol dependence or abuse and were included in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 72%
“…In regression analyses, borderline and histrionic were the only personality disorders features that contributed significant variance in suicidal ideation, whereas neuroticism was the only personality trait that contributed significant variance in suicidal ideation. 18 Here the researchers found highly significant (p=.0001) differences among cases and controls associated with adjustment disorder (case 29.2%, control 0.9%), mood disorder (case 12.4%, control 0.0%) and mood episode (case 8.0, control 0.9) . WHO/ISBRA study revealed the similar scenario, of the 1863 persons included in the WHO/ISBRA study, 292 had both a history of depressive symptoms and alcohol dependence or abuse and were included in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 72%
“…This study adds to the literature demonstrating strong psychometric properties for the GSIS among community-residing older adults (Marty et al 2010;Segal et al 2012), and provides evidence of strong internal consistency and construct validity for the EMIL, a new multidimensional measure of MIL developed to be consistent with Frankl's theory. The compelling findings of this study must nonetheless be considered in the context of its limitations, including cross-sectional data analysis, inclusion of largely healthy older adults, a primary reliance upon self-report data, and focus on suicide ideation rather than suicidal behavior.…”
Section: Discussionmentioning
confidence: 67%
“…The GSIS has demonstrated strong internal consistency among older adults (α = 0.91; Heisel and Flett 2006;Marty et al 2010) and significant 1-2 month test-retest reliability among nursing home residents (r = 0.86, p < 0.001; Heisel and Flett 2006). It has demonstrated criterion validity, differentiating mental health patients from nonpatients, construct validity with suicide ideation, hopelessness, depression, insomnia, impulsivity, poor coping strategies, and physical health complaints, and nonconvergence with MIL, PIL, psychological well-being, reasons for living, and subjective well-being (Heisel and Flett 2006Jahn et al 2011;Marty et al 2010;Nadorff et al 2013;Neufeld and O'Rourke 2009;Segal et al 2012). The GSIS has also shown sensitivity to clinical change in a small trial of Interpersonal Psychotherapy (IPT) adapted for older adults at-risk for suicide; study participants endorsed significantly less suicide ideation at posttreatment than at pretreatment assessment ).…”
Section: Methodsmentioning
confidence: 97%
“…The GSIS has demonstrated strong internal consistency for total (α=.93) and subscale scores (α=.82-.84), 1-2 month test-retest reliability (Pearson's r =.86 for the total scale and .75-.78 for the subscales, p <0.001; n =32), criterion validity differentiating mental health patients from non-patients, convergent validity with depression and hopelessness, and non-convergence with life satisfaction and psychological well-being [21,40,42-44]. The GSIS demonstrated strong internal consistency at this study's eligibility assessment for Total scores (α=.95; n =17), and Suicide Ideation (α=.88), Death Ideation (α=.90), Loss of Personal and Social Worth (α=.81), and Perceived Meaning in Life subscales (α=.90).…”
Section: Methodsmentioning
confidence: 99%